Do Investors Overrely on Old Elements of the Earnings Time Series?* - Bloomfield, Robert J.; Libby, Robert; Nelson, Mark W. (Contemporary Accounting Research, 2003)
Abstract This paper reports an experiment demonstrating that MBA students overrely on old earnings performance when predicting future earnings performance in a laboratory setting. In the experiment, MBA students relied too heavily on old annual ROE information to predict future annual ROE. The experiment shows how a common cognitive error (overreliance on unreliable information) interacts with the structure of the earnings time series to create particular patterns of prediction errors. The results also suggest directions for research on two well‐known anomalies, long‐run overreactions (De Bondt and Thaler 1985, 1987) and post‐earnings‐announcement drift (Bernard and Thomas 1990).